The second war among the members of the Abbas family (Damascus University Journal of Historical Studies, 2021)
This search treats the civilized second war among the members of the Abbas family which took place between Al-Masten and Al-Mataz in (251-252A.H/ 865- 866AM), The war continued for ten continuing months between Al-Masten who castled in Baghdad and the forces of Al-Mataz circled them, that was of reason of struggling and competition among the Turkish leaders for controlling on the caliph and behaving of its abilities. Baghdad and the areas which was surrounded by it, where were its square.The search define the two sides of fighting or conflicting and the main reasons which led it directly or indirectly. The prepares of the two sides for war, their forces of their elements, their origins, their armed, their military plans for each one of them, the events of war, its accidents according to its timed searl origin, then, their end, saved negotiation, the public role of war, their position of meeting. The reasons of failure of  Al-Masten, the effects, the reasons of that struggle on the areas which took place in it upon, the Abbas caliph and the areas which were followed to it.
Keywords: Abbas caliph, Al-Masten, Al-Mataz, Mohammad Ibn Abdullah Ibn Tahar